THE EFFECT OF MOTIVATION, WORK ENVIRONMENT, AND TRANSFORMATIONAL LEADERSHIP ON NURSE PERFORMANCE (CASE IN S HOSPITAL) - Phinari, Handelia; Innocentius Bernarto (Dinasti Publisher, 2020)
The purpose of this study was to determine the effect of motivation, work environment, and transformational leadership on the performance of nurses at S Hospital. This research was conducted in Denpasar, Bali, involving 55 nurses. Data collection was carried out by distributing questionnaires based on descriptive quantitative methods. Data were analyzed with the SmartPLS program. The results of this study stated that transformational leadership has a positive effect on nurse performance, motivation has a positive effect on nurse performance, work environment has a positive effect on nurse performance, transformational leadership has a positive effect on motivation, and transformational leadership has a positive effect on work environment.